Separation of silver from photographic wastes by emulsion liquid membrane system - Othman, Norasikin; Mat, Hanapi; Goto, Masahiro (Elsevier BV, 2006)
Separation of silver from liquid photographic waste containing various ions such as silver, ferum, sodium, and potassium by an emulsion liquid membrane containing Cyanex 302 as a carrier has been carried out. The important parameters governing the extraction behavior of silver have been investigated. These parameters were agitation speed, surfactant concentration, carrier concentration, type of diluents, treat ratio, and acid types in the stripping solution. The process has been conducted in a batch system using a mixer-settler. The results showed that the mobile carrier Cyanex 302 is selective towards silver compared to the other metals in the photographic waste. The highest silver extraction is obtained by using 0.05 M Cyanex 302, 3% (w/v) Span 80, 4.166 Hz (250 rpm) stirring speed, 1.0 M thiourea in 1.0 M H2SO4 stripping agent, 1:5 of treat ratio, and kerosene as a diluent.